Analysis of laboratory markers in body contouring procedures after bariatric surgery does not indicate particular risks for perioperative complications. - Stumpfe, Maximilian; Platzer, Juliane; Horch, Raymund E.; Geierlehner, Alexander; Arkudas, Andreas; Müller-Seubert, Wibke; Cai, Aijia; Promny, Theresa; Ludolph, Ingo (Perioperative Medicine, 2024)
BACKGROUND: Body contouring surgery after massive weight loss is associated with different risk factors. Wound healing disorders and seromas commonly occur postoperatively. Bariatric interventions lead to massive weight loss with excess skin and soft tissue. In this study, perioperatively collected laboratory markers of this special patient population were analyzed. METHODS: Fifty-nine patients were analyzed retrospectively regarding bariatric surgery, weight loss, body contouring surgery, laboratory markers, and complication rates. RESULTS: Body contouring surgery (n = 117) was performed in 59 patients. Weight loss was achieved after gastric bypass (40.1%), gastric banding (33.9%), or sleeve gastrectomy (26.0%), with an average of 69.2 kg. The most common body contouring procedure included abdominoplasty (n = 50), followed by thigh lift (n = 29), mammaplasty (n = 19), brachioplasty (n = 14), and upper body lift (n = 5). Analysis of laboratory markers revealed no exceptional and clinically relevant variations. Correlation analysis revealed associations between resection weight, amount of drain fluid, and particular laboratory markers. CONCLUSION: Analysis of perioperative laboratory markers in this special patient population after massive weight loss did not indicate clinically relevant risk factors regardless of the type of bariatric or body contouring surgery. Body contouring surgeries after bariatric interventions prove to be safe and low risk concerning perioperative laboratory markers and postoperative hospitalization.
EVALuna2:574369